α2- and β2-Adrenoreceptor-Mediated Efficacy of the Atypical Antidepressant Agomelatine Combined With Gabapentin to Suppress Allodynia in Neuropathic Rats With Ligated Infraorbital or Sciatic Nerve - M’Dahoma, Saïd; Poitevin, Matthieu; Dabala, Eric; Payan, Hugo; Gabriel, Cecilia; Mocaër, Elisabeth; Bourgoin, Sylvie; Hamon, Michel (Frontiers in Pharmacology, 2018)
Previous data showed that neuropathic pain induced by mechanical lesion of peripheral nerves has specific characteristics and responds differently to alleviating drugs at cephalic versus extracephalic level. This is especially true for tricyclic antidepressants currently used for alleviating neuropathic pain in humans which are less effective against cephalic neuropathic pain. Whether this also applies to the antidepressant agomelatine, with its unique pharmacological properties as MT1/MT2 melatonin receptor agonist and 5-HT2B/5-HT2C serotonin receptor antagonist, has been investigated in two rat models of neuropathic pain. Acute treatments were performed two weeks after unilateral chronic constriction (ligation) injury to the sciatic nerve (CCI-SN) or the infraorbital nerve (CCI-ION), when maximal mechanical allodynia had developed in ipsilateral hindpaw or vibrissal pad, respectively, in Sprague-Dawley male rats. Although agomelatine (45 mg/kg i.p.) alone was inactive, co-treatment with gabapentin, at an essentially ineffective dose (50 mg/kg i.p.) on its own, produced marked anti-allodynic effects, especially in CCI-ION rats. In both CCI-SN and CCI-ION models, suppression of mechanical allodynia by ‘agomelatine + gabapentin’ could be partially mimicked by the combination of 5-HT2C antagonist (SB 242084) + gabapentin, but not by melatonin or 5-HT2B antagonist (RS 127445, LY 266097), alone or combined with gabapentin. In contrast, pretreatment by idazoxan, propranolol or the β2 antagonist ICI 118551 markedly inhibited the anti-allodynic effect of ‘agomelatine + gabapentin’ in both CCI-SN and CCI-ION rats, whereas pretreatment by the MT1/MT2 receptor antagonist S22153 was inactive. Altogether these data indicate that ‘agomelatine + gabapentin’ is a potent anti-allodynic combination at both cephalic and extra-cephalic levels, whose action implicates α2- and β2-adrenoreceptor-mediated noradrenergic neurotransmission.